The Effect of Implementing Media Computer Based Instruction (Simulation Model) Towards Student’s Autonomy in Science Learning - Wiranda Bayu Aditama; Satya Sadhu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
Students’ autonomy toward teacher during the learning activities leads one-way learning. Consequently, students have less autonomy in the learning activities. Therefore, this research adressed to implement the media computer based instruction (simulation model) in improving the students’ autonomy in a science learning. The total participants in this research were 79 of the 4th grade students from a purposively primary schools during the first semester of 2018. They were divided into two groups, namely the experimental group (n=55) and the control group (n=24). The research used a pre-test post-test quasi-experimental method with a nonequivalent control group design. The students’ autonomy data were collected by using the observation sheet for each of post-test and pre-test which consisted of five aspects i.e. motivation, initiative, confidence, discipline, and responsibility. The independent sample t-test was used statistically to compare the average score of the students’ autonomy during the pre-test and post-test. The collected data were analyzed by using SPSS 11.0 statistics program. The findings of the research indicated that computer based instruction (simulation model) affects the students’ autonomy significantly in the science learning. Thus, the researcher believes in the further study, the computer based instructions (simulation model) can be intergrated with the model or method in the learning activity to improve the students’ autonomy in learning science.